Integrated GPR and laboratory water content measures of sandy soils: From laboratory to field scale. (20th January 2018) - Ercoli, M.; Di Matteo, L.; Pauselli, C.; Mancinelli, P.; Frapiccini, S.; Talegalli, L.; Cannata, A.
Highlights: Integrated analyses were performed to understand water content in unsaturated zone. We calibrated high-frequency GPR on a controlled soil column at laboratory scale. First reference permittivity values for sandy soils in Central Italy are given. Abstract: In this study, laboratory and GPR water content measurements on two sandy soils are compared. A robust procedure to constrain GPR surveys is provided, aiming to obtain accurate and reliable soil moisture information at the field scale. The application of the well-known Topp's equation, provided good results only for water contents (θv ) from 5 to 17%. Therefore, integrated analyses are mandatory to better understand the subsurface structures and the water content pattern in unsaturated zones. Data and results here presented represent the first reference for typical sandy soils outcropping in Central Italy, providing solid constraints for engineering and hydrogeological applications.